The influence of personal and organizational values on marketing professionals' ethical behavior - Akaah, Ishmael P. (Journal of business ethics, 1994)
The authors examine empirically the influence of personal and organizational values on marketing professionals' ethical behavior. The results indicate that personal and organizational values underlie differences in marketing professionals' ethical behavior, albeit “small” terms of the proportion of explained variance. The results also suggest the relationship between organizational values and ethical behavior to be significant. However, the same is not the case for the relationship between personal values and ethical behavior.